COMPARATIVE APPROACH: AUTONOMY IN REPRODUCTIVE HEALTH IN LATIN AMERICA - AIZENBERG, Dra. Marisa (MEDECINE LEGALE DROIT MEDICAL, 2025)
The approach to sexuality in the field of public policies is usually controversial, however, the guarantee of sexual and reproductive rights and the promotion of sexual and reproductive health have formed an integral part of the Regional Gender Agenda for the last 40 years. Reproductive health for the people, groups and communities of the region with a gender approach and without generating distinctions, presents a different maturational development in each country of the region, this work will reflect this data.